Review of Derek B. Scott, ed. 2000. Music, Culture, and Society: A Reader. New York: Oxford University Press - Taylor, Timothy D. (Current Musicology, 2000)
It is always easy to quibble with collections of previously published materials over the important writings that are excluded and those that are included. But Derek B. Scott clearly made some rather curious decisions in compiling this reader (decisions made in part, he tells us, because of the prohibitive cost of reprinting certain items).